Near-field interference map due to a dipolar emission near the edge of a monocrystalline gold platelet. (1st December 2022) - Abbasirad, N; Barreda, A; Arslan, D; Steinert, M; Chen, Y-J; Huang, J-S; Staude, I; Setzpfandt, F; Pertsch, T
Abstract: Point source excitation and point detection in the near-field provides new perspective to study the near-field optical phenomena of plasmonic nanostructures. Using the automated dual-tip scanning near-field optical microscope (SNOM), we have measured the optical near-field response of a dipolar emission near the edge of a monocrystalline gold platelet. The image dipole method was used to analytically calculate the interference pattern due to surface plasmon polaritons excited at the position of aperture tip and those reflected from edges of the gold platelet. The near-field enhancement was observed on the edges of the gold platelet. Our results verify that automated dual-tip SNOM is an intriguing technique for quantum plasmonic studies where deterministic coupling of quantum emitters and the detection of the near-field enhancement are of great interest.